STUDI PEMBELAJARAN NILAI KARAKTER TANGGUNG JAWAB DALAM KEGIATAN EKSTRAKURIKULER PALANG MERAH REMAJA DI SMA NEGERI 5 PEKANBARU - Finny Junika Junika; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research is in the background of a good character to prevent the phenomenon of declining moral decline. This research was conducted at SMA Negeri 5 Pekanbaru. Held in June 25 to 19 Agutus 2019. Population and samples as many as 54 people. Data analysis techniques using quantitative descriptive analysis. The results showed from the percentage of respondents gained answers to the character grades in the extracurricular activities of adolescent Red Cross in SMA Negeri 5 Pekanbaru. The disfigured variables consist of 2 (two) variables 1) learning the character value of responsibility in the extracurricular activities of the Red Cross teen in SMA Negeri 5 Pekanbaru which is 28.22% division of duty by the teacher/contractor high category. Variable 2) supporting factors of character value responsibility in the activities of extracurricular Red Cross adolescents in SMA Negeri 5 is 34.44% interest (interest) high category. The learning barrier factor for the character responsibility value in the extracurricular activities of adolescent Red Cross in SMA Negeri 5 Pekanbaru is 39.56% School (teaching method, building situation) very high category.Key Words : Character Of Responsibility, PMR Extracurricular